Characterization of the enteric virome of clinically healthy pigs around weaning on commercial farms in the Netherlands using next generation sequencing and qPCR - M.A.R. Schyns; R. van den Braak; J. Peijnenborg; S. Coppens; M. Deijs; M. G.J.M. Burggraaff; W. I. Kuller; S. Theuns; L. van der Hoek; A. de Groof (Porcine Health Management)
Abstract Background Enteric virus infections around time of weaning have always been related to pig diseases such as postweaning diarrhea. Little, however, is known about the virus infection pattern (species, timing and viral load) in clinically healthy pigs. Virus infections may help to train and shape the immune system and presumably only lead to clinical disease when uncontrolled. Next Generation Sequencing (NGS) is a relatively new technique that can uncover the composition of the enteric virome. This study describes the dynamics of the enteric virome in clinically healthy pigs using NGS and qPCR until 10 weeks of age. Methods Seven farms were selected based on the following criteria: diarrhea after weaning was visible in less than 5% of the pens, piglets reached 25 kg of body weight before 10 weeks of age and no antimicrobial batch treatment had been used on the farm for the last six months. Rectal swabs were taken in five different age groups: 2, 3.5, 5, 7 and 10 weeks of age, 10 piglets per age group, in a cross-sectional setup. Two NGS platforms were used to detect enteric viruses. Eleven virus-specific qPCRs were used to corroborate the results of the NGS analyses. Results Rotavirus A, Porcine Kobuvirus, Enterovirus G and Porcine Astrovirus 3 and 4 were first detected at two weeks of age, followed by detection of Porcine Astrovirus 5 at 3.5 weeks of age, just before weaning. One week after weaning, at 5 weeks of age, Porcine Astrovirus 3 was undetectable, but now Porcine Astrovirus 1 and 2 had successively made their entry. Although Rotavirus B & C, Porcine Sapelovirus and Porcine Sapovirus were already detected just before weaning, the amount of virus peaked one week after weaning. Rotavirus H was first detected one week after weaning and peaked at 7 weeks of age. Many viruses were cleared by the age of 10 weeks. Conclusions The timing and magnitude of subclinical enteric virus infections across farms were remarkably similar. Our study offers insight into the dynamics of enteric virome development in healthy pigs and provides essential context to NGS-based diagnostics.